Tradução integral das Heroides de Ovídio em dístico elegíaco vernáculo - Melo, João Victor Leite (2024)
Considering the idea that a significant part of the surviving elegiac corpus of the Augustan age (1st century BC), starring Propertius, Tibulus, Sulpicia and Ovid, is translated into Portuguese through a structural homological model of vernacular couplet, in which Latin hexameters and pentameters are transposed by the alternation of verses formed by twelve and ten poetic syllables, this thesis aims to demonstrate that, despite coexisting with other arrangements, this format represents a tradition and a translation school in the Portuguese language. For this purpose, our work is divided into two analytical approaches: the first is a diachronic approach, in which we gather and comment on examples of metrical versions of Ovidian elegiac works (between the 16th and 19th centuries), highlighting the heterogeneity of the modulations carried out in the Renaissance, Arcadianism and Romanticism; the second is a synchronic approach, in which we collected samples from several translators (between 1964-2022) who have in common the choice of the 12/10 pattern in transpositions of Latin elegies. Keeping in mind specific rhythmic and stylistic differences among each of the authors, the chronological analysis of these works and the theoretical paratexts that accompany them reveal that, for more than half a century, the search for structural homology with the Latin elegiac couplet, carried out by the vernacular couplet 12/10, manifests itself in the translations through five discursive characteristics: metric, rhythm, compensation, isostychy and polymetry. Therefore, using theoretical-methodological parameters, as well as practical examples offered by this historical and living tradition, we present, in the fourth part of the thesis, the twenty-one poems that compose Ovid‟s Heroides, fully translated with the referred model.